Dampak Konten Negatif Kecanduan Game Online Terhadap Komunikasi Remaja - Iqbal Ramadana (Sadida Islamic Communications and Media Studies, 2026)
Exposure to negative content of online games spread through social media has the potential to increase online game addiction and affect the communication patterns of teenagers in Banda Aceh. This study aims to examine the impact of negative content of online game addiction on adolescent communication. The theoretical basis used is Albert Bandura's social learning theory as a basis for explaining the process of observation and imitation of adolescent behavior towards digital content. The method used is a literature review supported by the method of recording and observing through direct observation of adolescents in several coffee shops in Banda Aceh. Data were obtained from various scientific publications in 2022-2026 and analyzed using a thematic analysis approach. The study was conducted because there are still limited studies that specifically link exposure to negative content from online games with changes in adolescent communication, while previous research focused more on behavioral and mental health aspects. The results showed that the majority of adolescents (70.2%) were at a moderate level of online game addiction, with indications of difficulty controlling the duration of play. As many as 55.9% of adolescents have poor family communication patterns, and 79.3% of adolescents with high-category addictions come from families with ineffective communication. This research emphasizes the importance of strengthening family communication, increasing digital literacy, parental supervision, and collaboration between the government, schools, and digital platforms in creating a safer media ecosystem for adolescents.